2015
DOI: 10.1093/brain/awv142
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the phenotypes of Dravet syndrome by gene deletion

Abstract: *These authors contributed equally to this work.Neurological and psychiatric syndromes often have multiple disease traits, yet it is unknown how such multi-faceted deficits arise from single mutations. Haploinsufficiency of the voltage-gated sodium channel Na v 1.1 causes Dravet syndrome, an intractable childhood-onset epilepsy with hyperactivity, cognitive deficit, autistic-like behaviours, and premature death. Deletion of Na v 1.1 channels selectively impairs excitability of GABAergic interneurons. We studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
139
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 38 publications
(104 reference statements)
8
139
0
Order By: Relevance
“…We used the Cre-Lox method to delete Na V 1.1 channels specifically in each of these interneuron classes [82]. We found that these interneurons are selectively involved in the different DS phenotypes (Table 1; [82]).…”
Section: Pathogenic Roles Of Major Interneuron Classes In Dsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used the Cre-Lox method to delete Na V 1.1 channels specifically in each of these interneuron classes [82]. We found that these interneurons are selectively involved in the different DS phenotypes (Table 1; [82]).…”
Section: Pathogenic Roles Of Major Interneuron Classes In Dsmentioning
confidence: 99%
“…We used the Cre-Lox method to delete Na V 1.1 channels specifically in each of these interneuron classes [82]. We found that these interneurons are selectively involved in the different DS phenotypes (Table 1; [82]). Deletion in PV interneurons causes pro-epileptic effects and autistic-like behavior, but not other phenotypes [82].…”
Section: Pathogenic Roles Of Major Interneuron Classes In Dsmentioning
confidence: 99%
See 3 more Smart Citations